Application of Lean Six Sigma methodology in the registration process of a hospital. Issue 5 (3rd June 2014) - Bhat, Shreeranga; Gijo, E.V.; Jnanesh, N.A.
Abstract : Purpose: – The purpose of this paper is to study the scope of Lean Six Sigma (LSS) strategy and to explore its successful deployment in the Indian healthcare sector. Design/methodology/approach: – The research reported in this paper is based on a case study carried out using the LSS DMAIC (Define-Measure-Analyze-Control) approach and its application in improving the registration process in the Health Information Department (HID) of a Medical College hospital in India. Findings: – The study describes improvements in the HID through the power of LSS. Cycle time of the process was reduced from three to 1.5 minutes and the SD was reduced to 21.2 from 61 seconds. The project has shown a 94 per cent reduction in patients' average waiting time. The study also reported a 91 per cent reduction in queue length and 48 per cent reduction in percentage of scheduled utilization of staff for the process. Research limitations/implications: – The paper is based on a single case study executed in a hospital and hence there is limitation in generalizing the specific results from the study. But the approach adopted and the learning from this study can be generalized. The study is of use to healthcare practitioners seeking to implement or develop LSS further in their organizations. Originality/value: – Although LSS being extremely successful in the last two decades, the application of LSS to the healthcare industry in general and HID in particular has been limited. This study illustrates how its application can improve the performance of the process and thus productivity in the department.